Proust's Recherche and Hegelian teleology - Peters, Julia (Inquiry, 2010)
The final volume of Marcel Proust's novel [Agrave] la Recherche du Temps perdu (Recherche) presents a striking puzzle. In this volume, the narrator Marcel proposes a literary theory which is supposed to provide the theoretical basis for the whole book, such that the Recherche can be considered a novel which contains its own theory. However, the Recherche as a whole does not seem to comply with this literary theory. I suggest in this paper that this puzzle can be solved by appreciating that Marcel's theory of literature, and his understanding of the way literature relates to his own life, is based on a Hegelian notion of teleology.